Comportamiento agronómico, sanitario y productivo de 41 cruces interclonales de cacao (Theobroma cacao L.) trinitario por nacional, en la cuenca alta del río Guayas. - Moran Moncayo, Fabiola Elizabeth (2017)
The aim of the research was to generate knowledge about the agronomic, sanitary and productive behavior of the 41 interclonal crosses evaluated in the Quevedo area by examining their environmental conditions that are potentially suitable for sowing this crop. The present research was carried out in the Experimental Farm "La Represa" of the Quevedo State Technical University (UTEQ) located in the 7.5 km Faita precinct of the Quevedo - San Carlos road, province of Los Ríos. A completely randomized design with 41 interclonal cocoa hybrids including a commercial control with 4 replicates was applied, each experimental unit consisted of 8 productive cocoa seedlings. To determine differences between measurements, the Tukey test was used at 5% probability (P≤0.05). Based on the results obtained in the research, it was possible to conclude that in the flowering variable T33 (DYRCYT-H-304) and fruiting variable T41 (JHVH-10-WITNESS) obtained the highest average. While in the sprout variable there was no significance. Regarding the health variables in witch's broom incidence, the T36, T33 and T35 had no incidence, whereas in T3 (DYRCYT-H-274) it was highly significant with an average of 43.00. The variables of which can be verified that the T1 (DYRCYT-H-272) in this investigation obtained higher averages in cherelles wilt with 17.50 and in ears with 6,00 unlike the remaining treatments. In the variable Mazorcas, T2 (DYRCYT-H-273) and T22 (DYRCYT-H-293) presented higher average (17.00 and 16.50 respectively) during the given investigation.